The Influence of Organizational Culture, Leadership Style, and Work Environment on Employee Performance at PT Perkebunan Nusantara IV Reg I Medan City - Annisa Helvira; M. Chaerul Rizky (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of organizational culture, leadership, and work environment on employee performance at PT Perkebunan Nusantara IV Reg I Medan City. The research method used is a quantitative method with an associative approach. The population of this study is all employees of PT Perkebunan Nusantara IV Reg I Medan City totaling 35 people, with a sampling technique, namely saturated samples. Data collection was carried out through a questionnaire with a Likert scale. Data analysis uses multiple linear regression analysis. The results of the study show that organizational culture, leadership, and work environment simultaneously have a positive and significant effect on employee performance. Partially, organizational culture, leadership and work environment have a positive and significant effect on employee performance. The adjusted R square value is 0.586, which means that 58.6% of the variation in employee performance can be explained by the variation of the three independent variables, namely organizational culture, leadership, and work environment. While the remaining 41.4% was explained by other variables that were not studied in this study.